Facts About Vitamins - R. Elaine Turner; Wendy J. Dahl (EDIS)
Vitamins are chemical compounds that the body uses in a variety of ways. We need to get vitamins from our diet because we can't make them in the body. There are 13 different vitamins that have been identified as important nutrients for humans.